2010
DOI: 10.1051/0004-6361/201015716
|View full text |Cite
|
Sign up to set email alerts
|

Analytical expressions for the deprojected Sérsic model

Abstract: The Sérsic model has become the standard for parametrizing the surface brightness distribution of early-type galaxies and bulges of spiral galaxies. A major problem is that the deprojection of the Sérsic surface brightness profile to a luminosity density cannot be executed analytically for general values of the Sérsic index. We use Mellin integral transforms to derive an analytical expressions for the luminosity density in terms of the Fox H function for all values of the Sérsic index. We derive simplified exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 41 publications
5
48
0
Order By: Relevance
“…The Wilson model is defined by an alternate modified isothermal sphere based on the ad hoc stellar distribution function of Wilson (1975), which has more extended envelope structures than the standard King isothermal sphere (Mclaughlin et al 2008). The Sérsic model has an R 1/n surface density profile, which is used for parameterizing the surface brightness profiles of early-type galaxies and bulges of spiral galaxies (Baes & Gentile 2011). However, Tanvir et al (2012) found that some classical GCs in M31 that exhibit cuspy core profiles are well fitted by the Sérsic model of index n ∼ 2 − 6.…”
Section: Structural Modelsmentioning
confidence: 99%
“…The Wilson model is defined by an alternate modified isothermal sphere based on the ad hoc stellar distribution function of Wilson (1975), which has more extended envelope structures than the standard King isothermal sphere (Mclaughlin et al 2008). The Sérsic model has an R 1/n surface density profile, which is used for parameterizing the surface brightness profiles of early-type galaxies and bulges of spiral galaxies (Baes & Gentile 2011). However, Tanvir et al (2012) found that some classical GCs in M31 that exhibit cuspy core profiles are well fitted by the Sérsic model of index n ∼ 2 − 6.…”
Section: Structural Modelsmentioning
confidence: 99%
“…The apparent axis ratio of the bulge q b is also a free parameter of the model. The 3D luminosity density corresponding to this intensity distribution on the sky can be expressed using complex special functions (Mazure & Capelato 2002;Baes & Gentile 2011;Baes & Van Hese 2011). To describe the surface brightness distribution of the threedimensional axisymmetric stellar disc, radiative transfer modellers usually use a 3D luminosity density model where the radial and vertical profile of the luminosity density are exponential (the double-exponential disc).…”
Section: Decomposition Of the Irac 36 µM Imagementioning
confidence: 99%
“…For the bulges, we assumed the traditional Sérsic profile (Sersic 1968;Caon et al 1993;Prieto et al 2001;Baes & Gentile 2011),…”
Section: Fitting Functionsmentioning
confidence: 99%